O evangelho segundo Saramago: uma Madalena não mais proscrita - Santos, Wilgner Murilo da Conceição (2018)
In theeighth novel publishedby José Saramago, thechristianmythisdeconstructedalongwith its celebratedprotagonists in ordertogivevoicetothosewho, in theprocessofreconstruction, do nothave it. Therefore, in thiswork, afterdiscussing some aspectsofthegenesisofthemythandthe social-historicalconfigurationsthatpotentialized a systematicsilencingofthefeminine in theOccident, weanalyze Mary of Magdala, a characterfromThe Gospel accordingto Jesus Christ (1991), in a comparativestudywiththoseofthe canonical andapocryphal gospels, in ordertolocatethefirst-century Mary Magdalene ofthe Christian Era in ordertounderstandherparticipationatthemovementthatwouldgiverisetooneofthegreatestreligionsoftheplanet. The analyzes are basedonthestudiesof Armstrong (2006), Brunel (2005), Crowley (2016), Blainey (2012), Delumeau (1989), Beauvoir (2016), Hutcheon (1989, 2000), Arnaut (2008), Ferraz (1998, 2012), Perrone-Moisés (1999), Martins (2014), Sebastiani (1995), Faria (2004), amongotherstudious. Alongtheway, we note thatwiththis book, thePortuguesewriternotonlyexposes a new andironicversionof a widelyknownstory, butalsopresents a subversiveMary Magdalene, which, in tune withrecentquestionsaboutearlychristianity, emerges as a womanwhoownsherself; thedescendantofEvefreedfromthedepreciativetraditionthathasmarginalizedher for centuries. At theendofthesepages, weseethatthesaramaguiancharactercanbe a reflectionoftheperson, because, withtheconfrontationofthegospels, wefindtheMagdalene companion, disciple, apostle, themotheroftheeuangélion